Menimbang Media Sosial dalam Marketing Politik di Indonesia: Belajar dari Jokowi-Ahok di Pilkada DKI Jakarta 2012 - Utomo, Wisnu Prasetya (Jurnal Ilmu Sosial dan Ilmu Politik, 2013)
The victory of Jokowi and Basuki Tjahaya Purnama (Ahok) in the 2012 Jakarta election has marked an important stage in the development of political marketing on contemporary Indonesian politics. Social media provides a great influence in this election. Social media became an effective tools to organize people and mobilize voters. In the era of political personalization after the authoritarian New Order, mix-mediated political marketing which combine social media, mass media, and traditional political marketing can be an alternative strategy for the candidate or political party to win the election.